Investigating the Psychological Determinants of the Intention to Use E-Hailing Service - Nur Zaimah, Binti Ubaidillah; Lim, Sien Nar; Rosita, Binti Hamdan; Liwan, Audrey; Farhana, Binti Ismail (Human Resource Management Academic Research Society (HRMARS), 2019)
The transportation industry has changed rapidly in recent years. The increased availability of location data and the increasing number of applications, together with other forms of information and communication technologies (e.g., e-commerce, telecommunication), are transforming transportation supply and demand in numerous ways. The integration of the global mobile positioning system (GPS) and electronic payment along with the continuous need for flexible travel has led to the Grab e-hailing service becoming one of the most prominent ondemand private driver platforms in the Asian region. Hence, this study aimed to examine the behavioral intentions of Generation Z to use the Grab e-hailing service. The study used 330 samples collected from undergraduate students in Malaysia. The collected data were analyzed using multiple regression analysis. The results showed that there is a significant relationship between the perceived price and advantages, perceived convenience, and perceived accessibility towards the behavioral intention to use the Grab e-hailing service. This research study offers useful and essential information for stakeholders to achieve a further understanding of the psychological determinants to address the needs of special interest group of end-users.